2004
DOI: 10.1055/s-2004-818499
|View full text |Cite
|
Sign up to set email alerts
|

Die nichtinvasive Beatmung bei Patienten mit stabiler, schwergradiger chronisch-obstruktiver Bronchitis und Lungenemphysem (COPD)

Abstract: Noninvasive positive pressure ventilation in patients with stable chronic obstructive pulmonary disease. The role of non-invasive positive pressure ventilation (NIPPV) is well documented in patients with restrictive thoracic diseases like kyphoscoliosis, tuberculosis sequelae or neuromuscular disease. There is also a good evidence for the use of NIPPV in acute respiratory failure in patients with an exacerbation of COPD. The application of NIPPV in patients with chronic respiratory failure is growing, but ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Therefore, some scholars believed that NPPV could benefit the patients with stable hypercapnic COPD by reducing the burden of respiratory muscle, relieving the fatigue and improving the gas exchange. 34 , 35 However, most of the previous RCTs could not reduce PaCO 2 significantly probably due to the low intermittent positive airway pressure (IPAP) of 10–20 cmH 2 O in NPPV. Current studies showed that IPAP in NPPV reaching 30 cmH 2 O could obviously improve the level of arterial blood gas in patients with stable hypercapnic COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some scholars believed that NPPV could benefit the patients with stable hypercapnic COPD by reducing the burden of respiratory muscle, relieving the fatigue and improving the gas exchange. 34 , 35 However, most of the previous RCTs could not reduce PaCO 2 significantly probably due to the low intermittent positive airway pressure (IPAP) of 10–20 cmH 2 O in NPPV. Current studies showed that IPAP in NPPV reaching 30 cmH 2 O could obviously improve the level of arterial blood gas in patients with stable hypercapnic COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies showed that IPAP in NPPV reaching 30 cmH 2 O could obviously improve the level of arterial blood gas in patients with stable hypercapnic COPD. 6 , 35 , 36 A long-term study carried out by Windisch et al 6 showed that NPPV targeted at greatly reducing hypercapnia (average IPAP =28 cmH 2 O) could significantly improve the levels of arterial blood gas and lung function of COPD patients with chronic respiratory failure and reduce the mortality to 86% in 2 years. Consistent with the abovementioned opinion, we found that high IPAP settings benefited patients more.…”
Section: Discussionmentioning
confidence: 99%
“…Indiziert ist eine solche Heimbeatmung bei einer symptomatischen Hyperkapnie mit einem Kohlendioxidpartialdruck über 55 mmHg, in Ausnahmefällen ist eine solche Behandlung bereits bei Werten über 50 mmHg indiziert (31). Empfehlenswert ist eine nächtliche Beatmung, damit tagsüber möglichst viel beatmungsfreie Zeit verfügbar ist (11).…”
Section: Druckbeatmung Stärkt Die Atemmuskulaturunclassified